Characterization of vB_StuS_MMDA13, a Newly Discovered Bacteriophage Infecting the Agar-Degrading Species Sphingomonas turrisvirgatae - Pasquale Marmo; Maria Cristina Thaller; Gustavo Di Lallo; Lucia Henrici De Angelis; Noemi Poerio; Federica De Santis; Maurizio Fraziano; Luciana Migliore; Marco Maria D’Andrea (Viruses, 2020)
Members of Sphingomonas genus have gained a notable interest for their use in a wide range of biotechnological applications, ranging from bioremediation to the production of valuable compounds of industrial interest. To date, knowledge on phages targeting Sphingomonas spp. are still scarce. Here, we describe and characterize a lytic bacteriophage, named vB_StuS_MMDA13, able to infect the Sphingomonas turrisvirgatae MCT13 type strain. Physiological characterization demonstrated that vB_StuS_MMDA13 has a narrow host range, a long latency period, a low burst size, and it is overall stable to both temperature and pH variations. The phage has a double-stranded DNA genome of 63,743 bp, with 89 open reading frames arranged in two opposite arms separated by a 1186 bp non-coding region and shows a very low global similarity to any other known phages. Interestingly, vB_StuS_MMDA13 is endowed with an original nucleotide modification biosynthetic gene cluster, which greatly differs from those of its most closely related phages of the Nipunavirus genus. vB_StuS_MMDA13 is the first characterized lytic bacteriophage of the Siphoviridae family infecting members of the Sphingomonas genus.